Employee adaptation as key activity in human resource management upon implementing and maintaining desired organisational culture - Stacho, Zdenko; Stachová, Katarína; Hudáková, Monika; Stasiak-Betlejewska, Renata (Serbian Journal of Management, 2017)
In order to achieve the greatest possible equivalence between human resources in a company and desired organisational culture elements declared by a company, it is necessary to interconnect activities within individual functions of human resource management with desired values, attitudes and work behaviour. Such an interconnection is crucial for a positive response of employees to a suitable organisational culture, its embedding in their behaviour and subsequent sharing and spreading of organisational values. This paper will specifically define individual activities related to the adaptation of employees which need to be carried out in this regard. Based on a research conducted between 2011 and 2013, the paper will also define the present state and level of focus of organisations operating in Slovakia on both organisational culture as a whole and organisational culture in the context of employee adaptation.